2010
DOI: 10.1021/om1010808
|View full text |Cite
|
Sign up to set email alerts
|

Biferrocene Amino Acid, a Ferrocenylogoue of Ferrocene Amino Acid: Synthesis, Cross-Linking, and Redox Chemistry

Abstract: Access of the novel biferrocene amino acid 7 is provided by two different routes, namely, via desymmetrization of a biferrocene and via palladium-catalyzed cross-coupling of two substituted ferrocenes. The dissymmetric biferrocene 7 is head−head coupled to ureylene-bridged bis(biferrocene) 9 and also head−tail coupled to amide-bridged bis(biferrocene) 14. The monomer 7 and the dimers 9 and 14 are oxidized to mixed-valent cations 7 + , 9 + , 9 2+ , and 14 2+ . The valencies are trapped in the solid state as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 96 publications
3
39
0
Order By: Relevance
“…Analogous to the IR-SEC experiments, the esters 1 – 4 were also probed by UV–vis-SEC investigations. The UV–vis spectra of 1 – 4 recorded in dichloromethane show the ferrocene ligand field absorption band at λ max = 444, 449, 455 and 457 nm, which is typically around λ max ≈ 440–490 nm [ 66 , 70 , 79 80 ] ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to the IR-SEC experiments, the esters 1 – 4 were also probed by UV–vis-SEC investigations. The UV–vis spectra of 1 – 4 recorded in dichloromethane show the ferrocene ligand field absorption band at λ max = 444, 449, 455 and 457 nm, which is typically around λ max ≈ 440–490 nm [ 66 , 70 , 79 80 ] ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Paramagnetic 1 H NMR spectroscopy was used to identify the localization of the ferrocenium site in 2 + . [11][12][13][14][15] Upon titration of 2 with substoichiometric amounts of iodine only resonances of protons H 13 , H 14 and H 15 (Scheme 1, ESI †) are affected suggesting spin density at the non-hydrogen bonded iron site. This is fully confirmed by DFT calculations on 2 + showing spin density at the non-hydrogen bonded iron site (FeÁ Á ÁN distance 3.54 Å; FeÁ Á ÁH distance 2.66 Å; Fig.…”
mentioning
confidence: 99%
“…Having shown that putative switch 3 undergoes reversible oxidation, we attempted to use the [36,49]. They report that, while partial oxidation causes the Fc signals to broaden and shift downfield, other resonances belonging to protons further from the FcA group remain sharp.…”
Section: Characterizing the Redox Properties Of Switch 3 By Chemical mentioning
confidence: 99%